Found architecture: interpreting a cup-marked outcrop in the southern Highlands of Scotland. (2nd January 2019) - Bradley, Richard; Watson, Aaron
ABSTRACT: The practice of field archaeology depends on the ability to distinguish between cultural and natural features of the landscape; the same is true of heritage management. Early antiquarians found it difficult to maintain this distinction before the development of the discipline of geology, and prehistoric communities may have experienced similar problems. That is not surprising since the distinction between nature and culture is a recent development in Western thought. Mounds, cairns, rock outcrops and glacially transported boulders must have been difficult to interpret, especially in regions where there is convincing evidence that ancient monuments were reused in the past. These observations are illustrated by a recently excavated site in Strathtay, Scotland, where a geological outcrop seems to have been treated as the remains of a megalithic tomb of Neolithic date. During the Early Bronze Age, the rock was embellished with a zone of cup marks directed towards the midsummer sunrise, a cairn was erected, quartz was extracted, and pieces of worked stone were deposited in cracks visible in the surface of the stone. Others were spread across the surface of the site. The site was treated as if it was a built structure of some antiquity. On analogy with objets trouvés, it can be described as an example of 'found architecture'.